ANALISIS SIFAT KIMIA TANAH GAMBUT YANG DIKONVERSI MENJADI PERKEBUNAN KELAPA SAWIT DI KABUPATEN KAMPAR - Tri Cahyo Nugroho; Oksana Oksana; Ervina Aryanti (Jurnal Agroteknologi, 2013)
The research was conducted on February to agustus 2013 in the Tambang and Tapung Districk, Kampar Regency, Riau Province. The purpose of this research was to observe changes of soil chemical properties from secondary peat forests wich was converted to oil palm plantations at 6th and 26th years. This study is conducture by observation and survey at 50 cm and 100 cm of depth. Chemical analysis of the soil included pH, total-N, P-bray, C-organic, Cation Exchange Capacity (CEC), and Basa Cations (K, Ca, Mg and Na). Results of the analysis showed converted of peat land to oil palm plantation cause an increase in pH (1.19%), reduction in C-organic (17.94%), N-total (62.54%), Mg-dd (62.54%) and Na-dd (0.13%). Increase occurred oil palm at 6th years for CEC by (11.87%), P-bray (3.35%), K-dd (0.05%) and Ca-dd (13.89%). Decline occurred oil palm at 26th years for the by CEC by (3.35%), P-bray (10.91%), K-dd (0.09%) and Ca-dd (63.2%).